MORPHOBIOLOGICAL STRUCTURE OF BREAD WHEAT (TRITICUM AESTIVUM L.) IN AZERBAIJAN - Kh. N. Rustamov (Вавиловский журнал генетики и селекции)
The article presents information on the distribution of bread wheat in South Caucasus, including Azerbaijan. The subspecies and varietal composition and history of traditional and newly bred varieties of bread wheat are considered. It is shown that ecotype-contrasting groups of varieties should be used to obtain reliable scientific results on the comparative study of physiological and biochemical characteristics.